2016
DOI: 10.1590/1678-4324-2016160356
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Malaxation Process using Major Aroma Compounds in Virgin Olive Oil

Abstract: Optimization of major aroma compounds in olive oils

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…According to Cevik et al [10] to obtain the maximum quantity of ( E )-2-hexenal, a lower temperature and long malaxation time should be used. We do not agree with the results obtained by Lukić et al [5], which indicated that ( E )-2-hexenal and 1-penten-3-one content increased with higher malaxation temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Cevik et al [10] to obtain the maximum quantity of ( E )-2-hexenal, a lower temperature and long malaxation time should be used. We do not agree with the results obtained by Lukić et al [5], which indicated that ( E )-2-hexenal and 1-penten-3-one content increased with higher malaxation temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…More than 180 different aromatic compounds have been identified in olive oils [9] but only a small fraction of the large number of volatile compounds present in olive oil actually contribute to its overall aroma. In addition, these compounds are responsible for the positive attributes of olive oils and are indicators of a high-quality EVOO [10]. Phenolic compounds play an important role in the intensity of the release of certain aroma compounds during the consumption of EVOO.…”
Section: Introductionmentioning
confidence: 99%
“…As for the "Oliva Bianca" in our analysis (Table 5), also Caponio et al (2014) [38] showed a percentage trans-2-hexenal that ranged between 76.11% and 78.87% in oil of Coratina cultivar depending on decanter processing parameters. Furthermore, Cevik et al (2016) [39] showed a concentration of trans-2-hexenal in the range of 48.45-78.64% for oil from spotted fruits, 32.11-74.52% for oil from purple fruits and 26.73-65.03% for oil from black fruit. This aldehyde is derived from the metabolism of α-linolenic acid through the lipoxygenase (LOX) pathway, which influences the taste of green, pungent, bitter fruity, apple, almond and cut grass [40,41].…”
Section: Aromatic Profilementioning
confidence: 99%
“…[ 15 ] revealed in their study that VOOs extracted at 35 °C could produce oils with certain chemical and sensory performance, although in this case it could not be considered as “cold pressing.” Several research have been performed to determine the influence of malaxation parameters on oil sterols, triterpene diols, and volatile aroma content distribution of different cultivars. [ 16–21 ] The rising of malaxation temperature has been reported to cause increasement in total sterol amounts, possibly due to the decrement in viscosity of the oil that promotes the extraction of sterols from the olive paste. [ 3 ] Malaxation time has been generally found to be ineffective on sterol profile of olive oils.…”
Section: Introductionmentioning
confidence: 99%